Causal associations of genetically predicted gut microbiota and blood metabolites with inflammatory states and risk of infections: a Mendelian randomization analysis - Liu, Yingjian; Zhu, Qian; Guo, Gongjie; Xie, Zhipeng; Li, Senlin; Lai, Chengyang; Wu, Yonglin; Wang, Liansheng; Zhong, Shilong (Frontiers in Microbiology, 2024)
Inflammation serves as a key pathologic mediator in the progression of infections and various diseases, involving significant alterations in the gut microbiome and metabolism. This study aims to probe into the potential causal relationships between gut microbial taxa and human blood metabolites with various serum inflammatory markers (CRP, SAA1, IL-6, TNFα, WBC, and GlycA) and the risks of seven common infections (gastrointestinal infections, dysentery, pneumonia, bacterial pneumonia, bronchopneumonia and lung abscess, pneumococcal pneumonia and urinary tract infections).Two-sample Mendelian randomization (MR) analysis was performed using inverse variance weighted (IVW), maximum likelihood, MR-Egger, weighted median, and MR-PRESSO.After adding other MR models and sensitivity analyses, genus Roseburia was simultaneously adversely associated with CRP (Beta IVW = -0.040) and SAA1 (Beta IVW = -0.280), family Bifidobacteriaceae was negatively associated with both CRP (Beta IVW = -0.034) and pneumonia risk (Beta IVW = -0.391). After correction by FDR, only glutaroyl carnitine remained significantly associated with elevated CRP levels (Beta IVW = 0.112). Additionally, threonine (Beta IVW = 0.200) and 1heptadecanoylglycerophosphocholine (Beta IVW = -0.246) were found to be significantly associated with WBC levels. Three metabolites showed similar causal effects on different inflammatory makers or infectious phenotypes, stearidonate (18:4n3) was negatively related to SAA1 and urinary tract infections, 5-oxoproline contributed to elevated IL-6 and SAA1 levels. In addition, 7-methylguanine showed a positive correlation with dysentery and bacterial pneumonia.This study provides novel evidence confirming the causal effects of the gut microbiome and the plasma metabolite profile on inflammation and risk of infections.These potential molecular alterations may aid in the development of new targets for the intervention and management of disorders associated with inflammation and infections.